2017
DOI: 10.1007/s10014-017-0288-6
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 K27M mutations in adult cerebellar high-grade gliomas

Abstract: Adult cerebellar high-grade gliomas (HGG) are rare and their molecular basis has not been fully elucidated. Although a diffuse midline glioma H3 K27M-mutant, a recently characterized variant of HGG, was reported to occasionally occur in the cerebellum, adult cases were rarely tested for this mutation; only five mutant cases have been reported to date. It currently remains unknown whether H3 K27M-mutant cerebellar gliomas share common histological features or have a uniformly dismal prognosis. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…[1][2][3][4]12 Because of its rarity, the nature of the cerebel- no tumors with an IDH1/2 mutation. 8 Nakata et al also detected two H3F3A K27M mutated tumors among 10 cerebellar high-grade glioma cases, 11 in which our two IDHmutated tumors were included. In diffuse glioma, the IDH status is essential for integrated diagnosis by the WHO classification system (2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4]12 Because of its rarity, the nature of the cerebel- no tumors with an IDH1/2 mutation. 8 Nakata et al also detected two H3F3A K27M mutated tumors among 10 cerebellar high-grade glioma cases, 11 in which our two IDHmutated tumors were included. In diffuse glioma, the IDH status is essential for integrated diagnosis by the WHO classification system (2016).…”
Section: Discussionmentioning
confidence: 99%
“…These tumor cells resembled epithelioid or rhabdoid cells. Tumor cells were also positive for IDH1 R132H (H09, monoclonal, 1:50; Dianova, Hamburg, Germany) ( 10,11 and revealed an IDH1 c.G395A (R132H) mutation (Fig. 2B) or features of high-grade astrocytoma such as oval nuclei and eosinophilic cytoplasm with processes.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…Curative surgery is not possible, radiation therapy provides only temporary relief, and chemotherapies have thus far proven wholly ineffective (2,3). The current World Health Organization (WHO) diagnostic classification of diffuse midline glioma (DMG) is now categorically defined by the presence of the H3K27M mutation (4), and the clinical relevance ascribed to this genetic lesion highlights its unifying role as the biologic driver across a range of midline glial tumors involving the thalamus, cerebellum, brainstem (DIPG), and spinal cord (5)(6)(7). The presence of the H3K27M mutation in these tumors conveys a uniformly dismal prognosis regardless of tumor location or histologic grade (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…Extracted DNA of the two components was amplified by polymerase chain reaction and then sequenced with primers for IDH1/2, TP53, TERT promoter and BRAF as described elsewhere . DNA sequencing demonstrated that each component harbored IDH1 G395A mutation and TERT promoter C228T mutation (Fig.…”
Section: Pathological Findingsmentioning
confidence: 99%